Modified fractional order sliding mode control for speed control of permanent magnet synchronous motor / Fardila Mohd Zaihidee - Fardila , Mohd Zaihidee (2020)
In recent years, energy saving research activities have focused on electric motors and their systems since they are the main consumer of electricity in the industrial sector. Permanent magnet synchronous motor is known as a high-efficiency motor and slowly replacing induction motors in the industries. For speed control of PMSM, the sliding mode controller (SMC) has been widely used due to its robustness, high accuracy, and simplicity. The main disadvantage of the SMC method is the chattering phenomenon, which should be reduced or eliminated without compromising the controller’s robustness. Fractional order sliding mode speed control (FOSMC) of PMSM is proposed in this research to overcome the above-stated problem. This controller incorporates fractional calculus which theoretically has a slower energy transfer compared to integer order calculus in order to suppress the chattering phenomenon. The stability of this controller is analysed using Lyapunov stability theorem. Firstly, the evaluation of the proposed controller is executed by simulation in MATLAB/Simulink environment. Then, a closed-loop PMSM drive prototype is developed to run experimental verification of the control system. The designed FOSMC provides a reference value for the current controller in the inner loop, which will then provide the required reference voltage for the PWM to generate switching signals for the inverter. With speed reference of 500 rpm, transient overshoot of only 8.18% is recorded in the experiment. When a load torque of 0.5 Nm is applied, the PMSM experiences only 9.36% of speed drop and then recovered back to the reference speed after 3.36 seconds. At a steady state, the speed command is tracked with only 1.14% error and low torque ripple of only 3.88%. Performance comparison with IOSMC shows that the proposed FOSMC system experiences up to 5 times less overshoot and up to 60% less speed drop. In addition, FOSMC with PID sliding surface as proposed resulted in less overshoot of up to 14% and less speed drop of up to 20% compared to FOSMC-PI and FOSMC-PD. In terms of torque ripple, the designed controller outperforms IOSMC and other FOSMCs with up to 7% and 23% less ripple respectively. Similarly, the current ripple of IOSMC is almost double the current ripple of FOSMC. On the other hand, when compared with FOSMC-PD, the proposed system experiences a 10% less current ripple. Simulation and experimental results prove that the proposed FOSMC speed controller performs as a robust and fast anti-disturbance controller to regulate the speed of a PMSM. In addition, it also has shown remarkable performance in terms of transient response and anti-disturbance properties compared to conventional integer order SMC. In its own fractional-order SMC group, the proposed controller has shown its advantages in balancing the individual strength and weaknesses of FOSMC-PI and FOSMC-PD. Small torque and current ripple prove that the chattering phenomenon has been successfully suppressed by this controller design. Hence, the proposed FOSMC is suitable to be used in a high-performance application of PMSM.